Recovery of Mineral Oil from Waste Emulsion using Electrocoagulation Method - Mohd Najib, Razali; Muhamed Yusuf, Shahul Hamid; Abdul Aziz, Mohd Azoddein (EDP Sciences, 2016)
This paper presents a research to recover mineral oil from industrial waste emulsion. This research also evaluates the standard of water produced after the oil recovery. The ecosystem could be polluted if this waste is not treated prior to discharge. The equipment needed for this experiment is power supply (generator), connecting wire and metal plate for providing the coagulant. The chosen plates were aluminium and iron plate. The power supply will be connected to the plate producing anode (positive terminal) and cathode (negative terminal). Both plates are immersed into a beaker containing waste emulsion. The charge supplied by the current will cause the aluminium or ferum to dissisipate and became ions. These ions will attract the oil to flock together and float at the surface. The water will then filter by using filter paper. Electrocoagulation was done without addition of chemical thus can prevent the hazard from the chemicals. The samples was sent for oil and grease test. The optimum time needed for recovery of oil was 3 hours. The percentage recovery reach constant trend ef 95% afterwards. When the power consumption increases, the percentage recovery also increases. However, the current should be lower than 0.5 ampere as it is the limit that human body can withstand. Thus, power consumption of 27.5 Watt was chosen as optimum value. The oil recovery of at power consumption at 27.5W is 96%. The best plate in the process was the aluminium pair which can recover more than ferum plate. The present work concludes the promising future for waste water treatment by usage of electrocoagulation technique.